2023
DOI: 10.1021/acsaem.2c04022
|View full text |Cite
|
Sign up to set email alerts
|

Steric Effect of N-Substituted Triphenylamine on Double-Anchored Phenothiazine Dye-Sensitized Solar Cells

Abstract: Bulky N-substituents of 4-(hexyloxy) phenyl-substituted and 4-(hexylthio)phenyl-substituted triphenylamine (TPA) were successfully introduced into double-anchored phenothiazine (PTZ) dyes (TY1−TY3) as capping moieties for metal-free organic sensitizers in dye-sensitized solar cells (DSSCs). Among TY dyes, the N-substituent of 4-(hexyloxy)phenylsubstituted TPA provided the best steric matching to its doubleanchored PTZ dye having a small π-bridge of thiophene (TY1) and thereby facilitated the most compact dye p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 47 publications
0
5
0
Order By: Relevance
“…The redox potentials of SD dyes were calculated by cyclic voltammetry and are displayed in Figure and Table . The first ground-state oxidation potential ( E HOMO ), calculated from the oxidation potential vs ferrocene/ferrocene + , was converted into the NHE upon the addition of 0.70 V. , The lowest unoccupied molecular orbital (LUMO) energy level of an ideal sensitizer should be situated above the TiO 2 conduction band for efficient charge injection, and the E HOMO of the sensitizer should be located below the redox function of the electrolyte for efficient dye regeneration. SD dyes have an E HOMO of 0.79–1.01 V, which is lower than the electrolyte redox function of liquid iodolyte with sufficient overpotential (∼400 mV) and, therefore, preferable for an efficient dye regeneration process.…”
Section: Resultsmentioning
confidence: 99%
“…The redox potentials of SD dyes were calculated by cyclic voltammetry and are displayed in Figure and Table . The first ground-state oxidation potential ( E HOMO ), calculated from the oxidation potential vs ferrocene/ferrocene + , was converted into the NHE upon the addition of 0.70 V. , The lowest unoccupied molecular orbital (LUMO) energy level of an ideal sensitizer should be situated above the TiO 2 conduction band for efficient charge injection, and the E HOMO of the sensitizer should be located below the redox function of the electrolyte for efficient dye regeneration. SD dyes have an E HOMO of 0.79–1.01 V, which is lower than the electrolyte redox function of liquid iodolyte with sufficient overpotential (∼400 mV) and, therefore, preferable for an efficient dye regeneration process.…”
Section: Resultsmentioning
confidence: 99%
“…As a result, DSSC with dye 73 exhibited a PCE of 10.47 % and 21.2 % under 1 sun and artificial light conditions respectively. [157] The chemical structures of metal free organic dyes consisting of cyanoacrylic acid anchoring unit are shown in Figures 11 -15 and their photovoltaic performance is tabulated in Table 2. ).…”
Section: Organic Dyes With Cyanoacrylic-acid Anchoring Unitmentioning
confidence: 99%
“…The hig obtained at 1000 lux for compound 2b reaching a η of 5.64%, with JSC of 59 445 mV, and FF of 0.74. In 2023, Li et al reported a series of sensitizers bearing a phenothiazine scaffold, arranged in a D(-π-A)2 skeleton [76]. A prelimin study was conducted under simulated AM 1.5 G illumination using mediator.…”
Section: Charge Extraction (Ce) Open-circuit Voltage Decay (Ocvd) And...mentioning
confidence: 99%
“…The authors also perfor study on the addition of the nonconductive co-adsorbent CDCA in comb finding that a high concentration of CDCA (CDCA/TY1 ≈ 33/1) is necessa occupy the TiO2 surface not covered by the dye, decreasing the aggrega molecules and leading to enhanced JSC. In 2023, Li et al reported a series of sensitizers bearing a double-anchored phenothiazine scaffold, arranged in a D(-π-A) 2 skeleton [76]. A preliminary photovoltaic study was conducted under simulated AM 1.5 G illumination using I − /I 3 − as a redox mediator.…”
Section: Charge Extraction (Ce) Open-circuit Voltage Decay (Ocvd) And...mentioning
confidence: 99%